Daily cannabis and reduced risk of steatosis in human immunodeficiency virus and hepatitis C virus‐co‐infected patients (ANRS CO13‐HEPAVIH). Issue 2 (20th November 2017) - Nordmann, S.; Vilotitch, A.; Roux, P.; Esterle, L.; Spire, B.; Marcellin, F.; Salmon‐Ceron, D.; Dabis, F.; Chas, J.; Rey, D.; Wittkop, L.; Sogni, P.; et al.
Summary: Liver steatosis is common in human immunodeficiency virus (HIV)‐hepatitis C virus (HCV)‐co‐infected patients. Some recent studies have found that cannabis use is negatively associated with insulin resistance in the general population and in HIV‐HCV‐co‐infected patients. Given the causal link between insulin resistance and steatosis, we hypothesized that cannabis use has a positive impact on steatosis. Therefore, we aimed to study whether cannabis use in this population was associated with a reduced risk of steatosis, measured by ultrasound examination. ANRS CO13‐HEPAVIH is a French nationwide multicentre cohort of HIV‐HCV‐co‐infected patients. Medical and socio‐behavioural data from clinical follow‐up visits and annual self‐administered questionnaires were prospectively collected. A cross‐sectional analysis was conducted using data from the first visit where both ultrasound examination data for steatosis (positive or negative diagnosis) and data on cannabis use were available. A logistic regression model was used to evaluate the association between cannabis use and steatosis. Among study sample patients (n = 838), 40.1% had steatosis. Fourteen per cent reported daily cannabis use, 11.7% regular use and 74.7% no use or occasional use ("never or sometimes"). Daily cannabis use was independently associated with a reduced prevalence of steatosis (adjusted odds ratio [95% CI] = 0.64 [0.42;0.99]; P = .046), after adjusting for body mass index, hazardous alcohol consumption and current or lifetime use of lamivudine/zidovudine. Daily cannabis use may be a protective factor against steatosis in HIV‐HCV‐co‐infected patients. These findings confirm the need for a clinical evaluation of cannabis‐based pharmacotherapies in this population. Eudract.ema.europa.eu number, DGS050367.